2016
DOI: 10.20409/berj.2016422335
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Aggregated-Disaggregated Energy Consumption and Economic Growth in Turkey

Abstract: Energy is recognized as an important factor in the production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Türkiye üzerine yapılan çalışmada Pata ve Terzi (2016), 1972-2011 dönemi için enerji tüketimi (petrol, elektrik, kişi başı ve toplam birincil enerji tüketimi, karbondioksit emisyonları) ile ekonomik büyüme arasındaki ilişkiyi Johansen Juselius eşbütünleşme testi, DLVAR, genelleştirilmiş etki-tepki ve varyans ayrıştırma analizleri aracılığıyla incelemişlerdir. Yazarlar, Johansen Juselius eşbütünleşme testinden enerji tüketimi ile ekonomik büyüme arasında uzun dönemli bir ilişki tespit edememişlerken, DLVAR analizinden kısa dönemde Türkiye ekonomisinin istikrarlı büyümesi için enerjinin önemli bir girdi olduğu sonucuna ulaşmışlardır.…”
Section: Ampirik Literatürunclassified
“…Türkiye üzerine yapılan çalışmada Pata ve Terzi (2016), 1972-2011 dönemi için enerji tüketimi (petrol, elektrik, kişi başı ve toplam birincil enerji tüketimi, karbondioksit emisyonları) ile ekonomik büyüme arasındaki ilişkiyi Johansen Juselius eşbütünleşme testi, DLVAR, genelleştirilmiş etki-tepki ve varyans ayrıştırma analizleri aracılığıyla incelemişlerdir. Yazarlar, Johansen Juselius eşbütünleşme testinden enerji tüketimi ile ekonomik büyüme arasında uzun dönemli bir ilişki tespit edememişlerken, DLVAR analizinden kısa dönemde Türkiye ekonomisinin istikrarlı büyümesi için enerjinin önemli bir girdi olduğu sonucuna ulaşmışlardır.…”
Section: Ampirik Literatürunclassified
“…She found that a unidirectional linear causality is moving from Y to EC at both aggregate and sectoral (residential, commercial and street illumination EC) levels, but a unidirectional NL causality is moving from commercial EC towards Y and from Y to EC for street illumination. Pata and Terzi (2016) employed Dolado-Lütkepohl Granger causality with SUR method from the period 1972 to 2011 and found that a positive unidirectional causality is moving from EC to GDP in the short run. Gokten and Karatepe (2016) used the data for the period of 1950-2010 by Dolado-Lütkepohl Granger causality, and concluded that there is a unidirectional causality is going from EC to GDP in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%